2021
DOI: 10.25115/eea.v40i1.5761
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Opportunity Exploration, Exploitation and Corporate Social Responsibilities on Sustainable Manufacturing Business Performance in Mekong River Delta

Abstract: A given business or market environment and corporate responsibilities always offers opportunities that have a direct impact on the sustainable business performance. Several scholars have researched on how to take advantage of these opportunities in creating sustainable business performance.  This study analyzes determinants of the exploration, business opportunity exploitation, corporate social responsibilities (CSR) and sustainable business performance of manufacturing industry based in the Mekong River Delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Opportunity exploration refers to the search for new ideas, methods or approaches to perform a task or to solve problems that are different from the usual way (Ngugi, 2021, Benitez, et al, 2018. The study by Tu, et al (2022) found that when employees have the opportunity exploration behaviour, the sustainable development of the company can be achieved or maintained and objectives can be achieved. The study by Matejun (2018) also found that opportunity exploration behaviour affects the competitive advantage of the company.…”
Section: Opportunity Exploration IImentioning
confidence: 99%
“…Opportunity exploration refers to the search for new ideas, methods or approaches to perform a task or to solve problems that are different from the usual way (Ngugi, 2021, Benitez, et al, 2018. The study by Tu, et al (2022) found that when employees have the opportunity exploration behaviour, the sustainable development of the company can be achieved or maintained and objectives can be achieved. The study by Matejun (2018) also found that opportunity exploration behaviour affects the competitive advantage of the company.…”
Section: Opportunity Exploration IImentioning
confidence: 99%